Zivilgesellschaft – zwischen Wirtschaft und Staat. Eine institutionenoekonomische Interpretation - Birger P. Priddat (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2004)
– "Civil society" seems like a new myth, but to explain it we need an institutional design, developed by Buchanan, Dixit and Barzel: third party enforcement (TPE). Traditionally TPE means the role of the state as a regulator or mediator of all transactional parties on the marketplace. In the context of the civil society TPE demonstrates the non-governmental role of governance, monitoring and governing the relationship between state and society or state and economy – by a third party: NGO i.e., other states, or international institutions like the UN etc. The text explains the institutional design of TPE and its relevance.
Keywords: 330